Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/107429561302300103
|View full text |Cite
|
Sign up to set email alerts
|

Students with Emotional and Behavioral Disorders as Peer Tutors: A Valued Role

Abstract: R ob is a sixth grade student in Ms. Decker's self-contained classroom for students with emotional and behavioral disorders (EBD). He has struggled in school, both academically and behaviorally, for as long as his family can remember. He was retained in kindergarten and first grade, and has failed to meet benchmarks on the annual state standardized test. Rob also engages in many escapemotivated behaviors. For instance, he flipped over his desk and punched a wall as others completed a benchmark reading test las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Specifically, following implementation in their classrooms, teachers felt that peer tutoring was a viable and effective instructional strategy that addresses not only the needs of students with learning difficulties but also helps in preserving a quality learning experience for typically developing students (Dufrene, Noell, Gilbertson, et al, ). Moreover, teachers in the study of Wang, Bettini and Cheyney () reported that peer tutoring proved particularly helpful in enhancing the social skills of students with emotional behavioural disorders. Similar positive experiences were detected in the study conducted by Jones (), in which school staff were found to be very positive towards peer tutoring mentioning various benefits for the participated students with autism.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, following implementation in their classrooms, teachers felt that peer tutoring was a viable and effective instructional strategy that addresses not only the needs of students with learning difficulties but also helps in preserving a quality learning experience for typically developing students (Dufrene, Noell, Gilbertson, et al, ). Moreover, teachers in the study of Wang, Bettini and Cheyney () reported that peer tutoring proved particularly helpful in enhancing the social skills of students with emotional behavioural disorders. Similar positive experiences were detected in the study conducted by Jones (), in which school staff were found to be very positive towards peer tutoring mentioning various benefits for the participated students with autism.…”
Section: Introductionmentioning
confidence: 99%
“…When establishing peers as models, it is important to directly teach the expected behaviors for both roles. That means stating the importance of performing each role, modeling the behaviors, providing corrective feedback when appropriate, reinforcing correct performance of the behaviors, and reteach role behaviors as necessary (Wang, Bettini, & Cheyney, 2014).…”
Section: Providing Modelsmentioning
confidence: 99%
“…Accordingly, disability specific information, like managing disruptive behaviour or provide physical assistance, should be offered to tutors during training (Bond & Castagnera, 2006;Lieberman, Dunn, Van der Mars, & McCubbin, 2000;Temple & Lynnes, 2008). As a conclusion, all authors argued that students should be able to follow and complete successfully all the procedures, before peer tutoring starts in their classrooms (Dufrene et al, 2010;Mackiewicz et al, 2011;Wang, Bettini, & Cheyney, 2013).…”
Section: Students' Trainingmentioning
confidence: 98%
“…In order to accomplish the aims of inclusion, various educational methods have been used through these years. One evidencebased intervention for providing supplemental instruction to students at risk or with SEND in mainstream classrooms is peer tutoring (Scruggs, Mastropieri, & Marshak, 2012;Wang, Bettini, & Cheyney, 2013;Wood, Mustian, & Lo, 2013). Klavina and Block (2013) suggested that peer tutoring can be used in mainstream classrooms to help students with SEND develop both their academic and social skills, along with the essential daily skills needed in their school routine.…”
Section: Peer Tutoring An Inclusive Meansmentioning
confidence: 99%
See 1 more Smart Citation